Ring 18 molecular assessment and clinical consequences. (22nd October 2014) - Carter, Erika; Heard, Patricia; Hasi, Minire; Soileau, Bridgette; Sebold, Courtney; Hale, Daniel E.; Cody, Jannine D.
<x xml:space="preserve">Abstract</x> Ring chromosome 18 is a rare condition which has predominantly been described by case reports and small case series. We assessed a cohort of 30 individuals with ring 18 using both microarray comparative genomic hybridization (aCGH) and fluorescence in situ hybridization (FISH). We determined that each participant had a unique combination of hemizygosity for the p and q arms. Four ring chromosomes had no detectable deletion of one of the chromosome arms using aCGH. However, two of these ring chromosomes had telomeric sequences detected using FISH. These data confirm the importance of molecular and cytogenetic analysis to determine both chromosome content and morphology. We failed to find dramatic changes in mosaicism percentage between cytogenetic measurements made at the time of diagnosis and those made years later at the time of this study, demonstrating that dynamic ring mosaicism is unlikely to be a major cause of phenotypic variability in the ring 18 population. Lastly, we present data on the clinical features present in our cohort, though the extreme genotypic variability makes it impossible to draw direct genotype‐phenotype correlations. Future work will focus on determining the role of specific hemizygous genes in order to create individualized projections of the effect of each person's specific ring 18 compliment. © 2014 Wiley Periodicals, Inc.